Temporal and spatial analysis of air temperature change trends (thermal anomalies) in the Kingdom of Saudi Arabia during the period 1985-2016 AD - Alshehri, Reem Mohammed (Journal of Humanities & Social Sciences, 2024)
This research deals with the temporal and spatial analysis of air temperature anomalies at the annual and quarterly levels of the climatic stations in the study area during the period (1985-2016), in addition to the analysis of the highest Super temperature and the lowest micro temperature during the time 1985-2016. The study stations differ in recording the degrees of thermal anomalies at annual and monthly rates due to the different conditions specific to each climatic station. Through the study, it was found that the rate of thermal anomalies at the annual level ranged between (-0.07 and 0.31 m°), and it was concluded that all stations experienced a positive increasing temperature anomaly except Jazan station, where the temperature decreased. At the quarterly level, there was a discrepancy in the amount of change between the seasons of the year; where the spring at Al - Jouf station recorded the highest increase in the amount of temperature change at an average of 0.30 m°, while it was found that the lowest rate of temperature change was the share of Riyadh station, reaching 0.30-m° in the same season. In general, winter is one of the highest seasons in thermal anomalies for most of the study stations; this indicates that the monthly temperature changes in winter are more than in summer, which was characterized by thermal stability. The research also addressed dealt with an analysis of the highest maximum temperature and the lowest minimum temperature; the study found that the highest maximum temperature during the study period was at Makkah station, reaching 51.4 m°, while Al-Jouf station recorded the lowest minimum temperature during the study period, reaching-7 m°.
Keywords: Thermal anomaly; air temperature; seasonal anomaly